Characteristics of the test that measure teacher's skills in identifying students with learning disabilities (A comparative study between classical theory and modern measurement theory) - Boubou, Mounzer; Charrouf, Ansab; Slman, Noura (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The current study aims to reveal the extent of the difference in meaning that can be given to the underlying trait through the degree that the individual gets by using both the traditional measurement theory and the response theory of the individual according to the mono-teacher model (Rush Model), and then search for justifications for the use of gradients according to any of The two theories in measurement and the intake on each of them, by comparing the differences in the characteristics of a test designed to reveal the skills of the class teacher in identifying students with learning difficulties when extracting these properties using both the traditional measurement theory and the response theory of the individual (modern theory) J Measurement and Evaluation). The designed test consisting of (60) individuals was applied to a sample of (300) class teachers. Initially, the quality of the test vocabulary properties was verified according to the conventional theory of measurement, and then by verifying that the vocabulary of the test conforms to the conditions of individual response theory. The difficulty coefficients extracted from both theories were then compared by calculating the correlation coefficients between them and revealing the significance of these coefficients using a t-test for correlation coefficients for the correlated samples. The results of the study indicated the absence of a statistically significant correlation between the values ​​of the coefficients, and the results indicated the presence of a statistically significant difference in the estimates of the parameters of the difficulty of the vocabulary between the two measurement theories. The study recommended that the use of singular response theory (binary and triple model) be expanded in extracting other test characteristics such as discrimination coefficients and guesswork coefficients that Rush model does not extract. تهدف الدراسة الحالية إلى التعرف على مدى الاختلاف في المعنى الذي يمكن اعطاؤه للسمة الكامنة من خلال الدرجة التي يحصل عليها الفرد باستخدام كل من نظرية القياس التقليدية ونظرية الاستجابة للمفردة وفق النموذج الأحادي المعلم (نموذج راش)، ومن ثم البحث عن التبريرات لاستخدام التدريجات وفق أي من النظريتين في القياس والمأخذ على كلٍ منها، وذلك من خلال مقارنة الفروق في خصائص اختبار مصمم للكشف عن مهارات معلم الصف في تعرّف التلامذة ذوي صعوبات التعلم وذلك عند استخراج هذه الخصائص باستخدام كلاً من نظرية القياس التقليدية ونظرية الاستجابة للمفردة (النظرية الحديثة في القياس والتقويم). تم تطبيق الاختبار المصمم والمؤلف من (60) مفردة على عينة مؤلفة من (300) معلم صف. تم في البداية التحقق من جودة خصائص مفردات الاختبار وفق النظرية الكلاسيكية في القياس ثم من خلال التحقق من مطابقة مفردات الاختبار لشروط نظرية الاستجابة للمفردة. تم بعد ذلك مقارنة معاملات الصعوبة المستخرجة من كلا النظريتين من خلال حساب معاملات الارتباط بينهما والكشف عن دلالة هذه المعاملات باستخدام اختبار (t-test) لمعاملات الارتباط للعينات المترابطة، وقد اشارت نتائج الدراسة إلى عدم وجود علاقة ارتباط دالة احصائياً بين قيم المعاملات كما أشرات النتائج إلى وجود فرق دال إحصائياً في تقديرات معالم صعوبة المفردات بين نظريتي القياس. أوصت الدراسة بأن يتم التوسع في استخدام نظرية الاستجابة للمفردة (النموذج الثنائية والثلاثية) في استخراج خصائص الاختبارات الأخرى مثل معاملات التمييز ومعاملات التخمين التي لا يستخرجها نموذج راش.